-(7y+3)-(-6y-4)=-3

Simple and best practice solution for -(7y+3)-(-6y-4)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(7y+3)-(-6y-4)=-3 equation:


Simplifying
-1(7y + 3) + -1(-6y + -4) = -3

Reorder the terms:
-1(3 + 7y) + -1(-6y + -4) = -3
(3 * -1 + 7y * -1) + -1(-6y + -4) = -3
(-3 + -7y) + -1(-6y + -4) = -3

Reorder the terms:
-3 + -7y + -1(-4 + -6y) = -3
-3 + -7y + (-4 * -1 + -6y * -1) = -3
-3 + -7y + (4 + 6y) = -3

Reorder the terms:
-3 + 4 + -7y + 6y = -3

Combine like terms: -3 + 4 = 1
1 + -7y + 6y = -3

Combine like terms: -7y + 6y = -1y
1 + -1y = -3

Solving
1 + -1y = -3

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + -1y = -3 + -1

Combine like terms: 1 + -1 = 0
0 + -1y = -3 + -1
-1y = -3 + -1

Combine like terms: -3 + -1 = -4
-1y = -4

Divide each side by '-1'.
y = 4

Simplifying
y = 4

See similar equations:

| 3+3m-1=9m+6-5m | | 3(5X+4)-10X+9=51 | | 17+3y=5 | | Y-25=180 | | -2(x-8)+9=25 | | Y-25+x+52+96=360 | | -5-3b=4(b+4) | | x+2x+4=10 | | X+52+96=180 | | 26-2a=-2(6a+3)+2 | | y=1.5x-0.4 | | 4(2x+1)-3x=34 | | 3s+8=-9s | | 5x^5=20x^3 | | 2x^2-15x+27=0 | | 4x+2*8=9*4x | | -2(7r+1)-6=-64 | | 2x^2-7x+9=x+1 | | -7.5x=15.0 | | -36=-v+8(v-8) | | 5y=10x-15 | | 162=6x+6(x+7) | | x^2-18x+70=0 | | 6x-7y=49 | | 16-6b=8-7b | | 2x+4x+3x+5=50 | | 0.3n=12 | | 2x-50+4x-63+3x+20=360 | | 0.3=12 | | -3x+2=-8 | | x-7.2=-3.1 | | 11x+18=10x+4 |

Equations solver categories